2016
DOI: 10.15517/rbt.v64i3.20901
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the ancestry for the variability of the Drug-Metabolizing Enzymes CYP2C9, CYP2C19 and CYP2D6 polymorphisms in a multiethnic Costa Rican population

Abstract: CYP2C9, CYP2C19 and CYP2D6 metabolize around 40% of drugs and their genes vary across populations. The Costa Rican population has a trihybrid ancestry and its key geographic location turns it into a suitable scenario to evaluate interethnic differences across populations. This study aims to describe the diversity of CYP2C9, CYP2C19 and CYP2D6 polymorphisms in Costa Rican populations in the context of their ancestry. A total of 448 healthy individuals were included in the study: Bribri (n= 47), Cabécar (n= 27),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, the frequency of genetic variants as well as their distribution and combination within a haplotype may differ in admixed populations when compared with parental populations. For example, CYP2C19 has a higher number of rare genetic variants in Hispanics (4%), a highly admixed population, when compared with Europeans (0.05%), and CYP2C19*2 and *17 were found at a higher frequency in self‐reported Afro‐Caribbean subjects from Costa Rico than mestizos of the same country 72,73 . In addition, frequencies may also profoundly differ among indigenous populations, including those in North, South, and Central America 74–76 …”
Section: Cyp2c19 Allele Genotype and Phenotype Frequencies Across Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the frequency of genetic variants as well as their distribution and combination within a haplotype may differ in admixed populations when compared with parental populations. For example, CYP2C19 has a higher number of rare genetic variants in Hispanics (4%), a highly admixed population, when compared with Europeans (0.05%), and CYP2C19*2 and *17 were found at a higher frequency in self‐reported Afro‐Caribbean subjects from Costa Rico than mestizos of the same country 72,73 . In addition, frequencies may also profoundly differ among indigenous populations, including those in North, South, and Central America 74–76 …”
Section: Cyp2c19 Allele Genotype and Phenotype Frequencies Across Pmentioning
confidence: 99%
“…For example, CYP2C19 has a higher number of rare genetic variants in Hispanics (4%), a highly admixed population, when compared with Europeans (0.05%), and CYP2C19*2 and *17 were found at a higher frequency in self-reported Afro-Caribbean subjects from Costa Rico than mestizos of the same country. 72,73 In addition, frequencies may also profoundly differ among indigenous populations, including those in North, South, and Central America. [74][75][76] Considering CYP2C19*1 through *35 (excluding the CYP2C19*36 and *37 deletion alleles), hundreds of allele REVIEW combinations are possible, and thus, the number of genotypes in a population or patient cohort can be quite large.…”
Section: Cyp2c19 Allele Genotype and Phenotype Frequencies Across Pmentioning
confidence: 99%
“…The high percentages of the nullactivity alleles *4 and *5 in Bribri account for its highest percentage of CYP2D6 gPMs in our Ibero-American dataset (21.7%). 17 Importantly, although the *4 allele is common and cosmopolitan, allele *5 is rarer worldwide. Our studied populations with > 90% of Native American ancestry host 31 copies of the CYP2D6*5 allele, whereas given its low frequency in Europeans (~2%) we would expect only 2.4 copies if all these alleles would have been the product of European introgression.…”
Section: Association Of Cyp2d6 Alleles and Predicted Metabolic Phenot...mentioning
confidence: 99%
“…A study in 1827 patients showed that over 90% reported at least one drug-induced side effect and high levels of distress (1). When patients suffer from one movement disorder, the chances of developing a second or third movement disorder are increased (71). These side effects impair their psychosocial functioning and quality of life (1).…”
Section: Severe Mental Illness and Measures Of Functioningmentioning
confidence: 99%